GENETIC CRITERIA FOR PREDICTING COMPLICATED GASTRIC AND DUODENAL ULCER - Mavlyanov, A.R.; Karimov, H.Y.; Alimov, S.U.; Mavlanov, J.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
The article is devoted to the study of the role of kinetic factors in the development of ulcerative complications in patients with peptic ulcer of the stomach and duodenum. Studies by local and foreign authors on genetic factors in patients with peptic ulcer of the stomach and duodenum were studied by their relationship between peptic ulcer of the stomach and duodenum.